Quantitative analysis of ecological compensation in the Yangtze River Delta region based on the value of ecosystem services and ecological footprint - Mao, Chunmei; Niu, Junjun (Frontiers in Ecology and Evolution, 2024)
The Yangtze River Delta is where "the Belt and Road" and China's Yangtze River Economic Belt converge, which plays a crucial strategic location. However, with the demands of economic growth, environmental issues are frequently present in the Yangtze River Delta as a result of human and exploitation of ecological resources, and there is an urgent need to coordinate the relationship between human development and ecology. In this context, the Yangtze River Delta region is used as the research subject, quantitatively analyzing various ecosystems within the region from three dimensions: ecosystem services value, ecological carrying capacity, and ecological footprint, and analyzing various factors that affect economic and environmental balance. Then calculate eco-compensation and its payment order based on this information, in order to build a foundation for coordinating ecological interests and safeguarding the environment in the Yangtze River Delta region. Specific research results: (1) Jiangsu Province was the main provider of ecosystem services in the Yangtze River Delta; the Yangtze River Delta's three main ecosystems-waters, forests, and wetlands-accounted for 90% of the ecosystem services valued in the area and must be preserved. (2) The Yangtze River Delta as a whole belonged to an ecological deficit area, showing varying degrees of unsustainable development; In terms of ecological deficits, cultivated land and fossil energy had the worst, and both need to be treated severely. (3) The Yangtze River Delta was a region that paid ecological compensation. The payment order and total amount was 6825.596 billion yuan in Shanghai, 6412.264 billion yuan in Jiangsu, 12088.852 billion yuan in Zhejiang, and 3675.637 billion yuan in Anhui. At the same time, considering the current state of Anhui, the amount of eco-compensation can be appropriately reduced.Finally, recommendations are made based on the findings above, in order to improve the overall ecological benefits of the Yangtze River Delta region and foster ecological integration, all provincial and municipal governments should take reasonable action to reverse the ecological deficit of fossil energy and cultivated land, and also aim to achieve an ecological surplus in both land uses.